Examining the Impact of Online Public Access Catalogue on Information Access and Utilization in Academic Library: A Case Study of Bishop Barham University College Library, Southwestern-Uganda. - Kyarisiima, Josephine (Kabale University, 2023)
The purpose of the study was to examine the examine the impact of online public access catalogue on information access and utilization at Bishop Barham University library. The study's specific objectives were to find out the role of online public access catalogue on information access and utilization, identify the challenges faced by the users in online public access catalogue to access information and utilization, and suggest possible solutions to challenges encountered by online public access catalogue on information access and utilization at Bishop Barham University library. The study used a mixed research design utilizing both qualitative and quantitative approaches. Using simple and purposive sampling techniques, a total of 100 respondents were selected to participate in this study. The questionnaires used by the researcher were both open-ended and closed-ended. The study was conducted in the period of 9 months from April to February 2023. The study findings concluded that the majority of the respondents answered that the online public access catalog equips library users with retrieval skills and explains the role of the online public access catalog on information access and utilization at the Bishop Barham University library. On the challenges faced by the users of the online public access catalog to access information and utilization, it was concluded that most of the respondents answered that network failure was the challenge facing the utilization of the online public access catalog to access information and utilization. On the suggestion of possible solutions to challenges encountered by the online public access catalog on information access and utilization, it was concluded that most respondents answered that offering training sessions to faculty members of libraries improves the online public access catalog on information access and utilization. There is need for staff training to enable them access and utilize online information resources.